Do pharmacist‐led medication reviews in hospitals help reduce hospital readmissions? A systematic review and meta‐analysis. (29th September 2016) - Renaudin, Pierre; Boyer, Laurent; Esteve, Marie‐Anne; Bertault‐Peres, Pierre; Auquier, Pascal; Honore, Stéphane
Abstract : Aims: The aim of this meta‐analysis is to examine the impact of in‐hospital pharmacist‐led medication reviews in paediatric and adult patients. Methods: Relevant studies were identified from the Medline and Cochrane Library databases. Studies were included if they met the following criteria (without any language or date restrictions): design: randomized controlled trial; intervention: in‐hospital pharmacist‐led medication review (experimental group) vs. usual care (control group); participants: paediatric or adult population. The primary outcome was all‐cause readmissions and/or emergency department (ED) visits at different time points. The secondary outcomes were all‐cause readmissions, all‐cause ED visits, drug‐related readmissions, mortality, length of hospital stay, adherence and quality of life. We calculated the relative risk (RR) or mean differences (MD) with 95% confidence intervals (CIs) for each study. We used fixed and/or random effects models. Heterogeneity was assessed using the I 2 statistic. Results: We systematically reviewed 19 randomized controlled trials (4805 participants). The readmission rates did not differ between the experimental group and the control group (RR = 0.97, 95% CI 0.89; 1.05, p  = 0.470). The secondary outcomes did not differ between the two groups, except for in drug‐related readmissions, which were lower in the experimental group (RR = 0.25, 95% CI 0.14; 0.45, p  < 0.001), and all‐cause ED visits (RR = 0.70, 95% CI 0.59; 0.85 p  = 0.001). Conclusion: The low‐quality evidence in this analysis suggests an impact of pharmacist‐led medication reviews on drug‐related readmissions and all‐cause ED visits. Few studies reported on adherence and quality of life. More high‐quality randomized clinical trials are needed to assess the impact of pharmacist‐led medication reviews on patient‐relevant outcomes, including adherence and quality of life.